2020
DOI: 10.1111/gbb.12712
|View full text |Cite
|
Sign up to set email alerts
|

Spatial reference learning deficits in absence of dysfunctional working memory in the TgF344‐AD rat model of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized by cognitive disorders and alterations of behavioral traits such as anhedonia and anxiety. Contribution of nonphysiological forms of amyloid and tau peptides to the onset of neurological dysfunctions remains unclear because most preclinical models only present one of those pathological AD‐related biomarkers. A more recently developed model, the TgF344‐AD rat has the advantage of overexpressing amyloid and naturally developing tauopathy, thus making it close to human fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…ns, not significant. *p 0.05, **p 0.01. memory in a Y-maze (Tournier et al, 2020). Together, these data suggest that compensatory mechanisms must be maintaining function, but certain tasks may be more vulnerable to deterioration.…”
Section: Resultsmentioning
confidence: 84%
“…ns, not significant. *p 0.05, **p 0.01. memory in a Y-maze (Tournier et al, 2020). Together, these data suggest that compensatory mechanisms must be maintaining function, but certain tasks may be more vulnerable to deterioration.…”
Section: Resultsmentioning
confidence: 84%
“…Despite significant AD pathology and altered synaptic function beginning at 6 months of age in TgF344-AD rats (23, 34), performance in hippocampus dependent spatial tasks such as Morris Water Maze or Barnes Maze is surprisingly not different from Wt (6163). At 9-months of age reference memory in a T-maze is altered, but not working memory in a Y-maze (64). Together, these data suggest compensatory mechanisms must be maintaining function, but certain tasks may be more vulnerable to deterioration.…”
Section: Resultsmentioning
confidence: 99%
“…The recent report showing a reduction in the participation of TgF344-AD rats in behavioural tests also supports the presence of a deficit in the dopaminergic system. 50 As it was previously reported that SSRI treatment can alter the activity of DA neurons, 69 we tested the impact of chronic exposure to citalopram on the response to quinpirole alone or in combination with MDLl00.907. The SSRI treatment appeared to be effective on reducing anxiety levels, and on the control of 5HT 2A R on the locomotor response to presynaptic quinpirole, but does not allow a normalization of the hyper-sensitivity of D 2 -autoreceptors.…”
Section: Discussionmentioning
confidence: 99%